If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -1) + (x + -3) = 5 Reorder the terms: 3(-1 + x) + (x + -3) = 5 (-1 * 3 + x * 3) + (x + -3) = 5 (-3 + 3x) + (x + -3) = 5 Reorder the terms: -3 + 3x + (-3 + x) = 5 Remove parenthesis around (-3 + x) -3 + 3x + -3 + x = 5 Reorder the terms: -3 + -3 + 3x + x = 5 Combine like terms: -3 + -3 = -6 -6 + 3x + x = 5 Combine like terms: 3x + x = 4x -6 + 4x = 5 Solving -6 + 4x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4x = 5 + 6 Combine like terms: -6 + 6 = 0 0 + 4x = 5 + 6 4x = 5 + 6 Combine like terms: 5 + 6 = 11 4x = 11 Divide each side by '4'. x = 2.75 Simplifying x = 2.75
| Y-919/-11=-4 | | m(-m+1)= | | 10+7m=6-5m | | 162/3*55/7 | | 38=2w | | 7y+3(y-8)=5(y+2)-3 | | 7.50*73.33-100=450 | | 2/3x+4/9=5/18x-8/9 | | 2k-5=13 | | 14x*14x=-21x | | 48-n=4(n-7) | | 46+12p=-686 | | 13+q/4=-3 | | 7/5=21/a | | 1/4*4/5 | | 55+23n=768 | | 7(y-3)/3=-4y | | 7-3(5t-10)=10 | | 18x*18x=15x | | 3(x+3)+2=9+2 | | 6/9=d/24 | | P/30+183=192 | | d/9=8 | | 7.50b-100=450 | | 10x-2x-3=4 | | K+174/13=26 | | 10/5=8/y | | 4x+2y+3y+7x= | | y-2(4)=0 | | 6x-36x=48-0.1 | | m=1/4 | | 12x=6x+9 |